The Implementation of Civic Education as a Means of Internalizing Nationalism to Primary School Students - Saputro, Inoe; Winarni, Retno; Indriayu, Mintasih (Universitas Pendidikan Ganesha, 2021)
Globalization not only affects positively the technology development, but also can affect negatively the character of young generation. It is here that civic education is very desirable as a measure of internalizing nationalism values, so that although young generations have global competencies, they remain to maintain nationalistic values. This research aims to describe the role of teachers as the instructor of civic education in internalizing nationalism values to primary school students. This was a descriptive qualitative research with 25 5th (fifth) graders in public primary schools in Surakarta, Central Java, Indonesia being the sample. Techniques of collecting data used were observation, questionnaire, and interview. Source and technique triangulations were used to validate the data. The result of research showed that teachers’ intervention is very vital to students’ nationalistic values. The data shows that 72% of students have high enthusiasm with discussion, 82% are very tolerant to diversity, and 80% love Indonesian original products. It indicates that teachers’ intervention also contributes to reducing the negative effect of globalization, directly determining the students’ nationalistic attitude.